PENGARUH CITRA MEREK ,KESESUAIAN HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA PENGGUNA APLIKASI SHOPEE - argona, argona (JURNAL EKOBIS DEWANTARA, 2024)
This research analyzes the influence of brand image, price suitability and promotion on students' purchasing decisions using the Shopee application. This research aims to examine the influence of brand image, price suitability and promotion on purchasing decisions. This research was conducted on 100 respondents using the Shopee application among students. Data collection was carried out by distributing questionnaires with a scale of 1-5 points to measure indicators. The analysis technique used in this research is descriptive analysis.